"Double‐hit" chronic lymphocytic leukemia: An aggressive subgroup with 17p deletion and 8q24 gain. Issue 3 (18th December 2017) - Chapiro, Elise; Lesty, Claude; Gabillaud, Clémentine; Durot, Eric; Bouzy, Simon; Armand, Marine; Le Garff‐Tavernier, Magali; Bougacha, Nadia; Struski, Stéphanie; Bidet, Audrey; Laharanne, Elodie; Barin, Carole; et al.
Abstract: Chronic lymphocytic leukemia (CLL) with 17p deletion (17p‐) is associated with a lack of response to standard treatment and thus the worst possible clinical outcome. Various chromosomal abnormalities (including unbalanced translocations, deletions, ring chromosomes and isochromosomes) result in the loss of 17p and one copy of the TP53 gene. The objective of the present study was to determine whether the type of chromosomal abnormality leading to 17p‐ and the additional aberrations influenced the prognosis in a series of 195 patients with 17p‐CLL. Loss of 17p resulted primarily from an unbalanced translocation (70%) with several chromosome partners (the most frequent being chromosome 18q), followed by deletion 17p (23%), monosomy 17 (8%), isochromosome 17q [i(17q)] (5%) and a ring chromosome 17 (2%). In a univariate analysis, monosomy 17, a highly complex karyotype (≥5 abnormalities), and 8q24 gain were associated with poor treatment‐free survival, and i(17q) ( P  = .04), unbalanced translocations ( P  = .03) and 8q24 gain ( P  = .001) were significantly associated with poor overall survival. In a multivariate analysis, 8q24 gain remained a significant predictor of poor overall survival. We conclude that 17p deletion and 8q24 gain have a synergistic impact on outcome, and so patients with this "double‐hit" CLL have a particularly poor prognosis. Systematic, targeting screening for 8q24 gain should therefore be considered in cases of 17p‐ CLL.